The use of different 17β-estradiol hormone doses and water temperatures to control cannibalism in catfish Clarias gariepinus seed - Hylda Khairah Putri; Muhammad Zairin Jr.; Odang Carman; Iis Diatin (Jurnal Akuakultur Indonesia)
Cannibalism is a major problem in the intensive catfish hatchery that caused high mortality. This phenomenon is allegedly due to the high level of testosterone hormones in the early larvae and seed stages. Testosterone is a maternal steroid hormone that is transferred directly by the parent to the egg. Catfish broodstock has high testosterone levels during the gonad maturation phase and it enters the eggs during the process of vitellogenesis. A high level of testosterone is considered to cause catfish seeds to behave aggressively and subsequently encourage cannibalism. This testosterone level may be reduced by estrogen through a negative feedback mechanism. This experiment aimed to evaluate the use of several 17β-estradiol doses at different water temperatures to control cannibalism in catfish seeds. This experiment used two factors, i.e. 17β-estradiol doses (0, 20, and 50 mg/kg) coated in the diet and water temperatures (28 and 31°C). The results showed that 17β-estradiol levels in catfish seeds increased with increasing experimental length. The use of 17β-estradiol at low water temperature (28°C) was better in decreasing mortality, while the dose of 50 mg/kg17β-estradiol which applied at 28°C was the best combination in controlling cannibalism on catfish seeds.